Bony Erosion with Mucoid Degeneration of the Anterior Cruciate Ligament - Ueda, Yusuke; Saita, Kazuo; Yamaguchi, Takehiko; Sekiya, Hitoshi; Akiyama, Toru (The Journal of Knee Surgery Reports, 2015)
Mucoid degeneration of the anterior cruciate ligament (MDACL) is a comparatively rare pathological finding in clinical practice. Its pathophysiology is still unclear. MDACL can be suspected in patients with knee pain associated with a thickened ACL. Treatment involving arthroscopic resection of the yellow mucoid substance is efficient for relieving the symptoms. Only few reports had mentioned about the association with the erosion of adjacent bone. Here, we describe the cases of our two MDACL patients with osseous erosion. Both the patients had suffered from posterior knee pain for several months. Magnetic resonance imaging (MRI) indicated a thickened ACL with increased signal with bone erosion on T2-weighted images. On arthroscopy, the ACLs were found to be grossly hypertrophied, and the region of the posterolateral bundle was impinged in both the patients. No bony pathological findings were observed by arthroscopy. The yellowish degenerated portion of the ACL was resected to resolve the pathological situation in each case. Postoperatively, both the patients had a full range of painless motion with no impediments to the quick resumption of daily living. Follow-up MRIs showed reduced volumes of bone erosion. Thus, bone erosion was not the main cause of the knee pain, but rather was a lesion associated with MDACL.
Keywords: knee; anterior cruciate ligament; mucoid degeneration; bone erosion